Studi Deskriptif Penggunaan Software IKMS® dalam Perencanaan Manajemen Bimbingan dan Konseling - Hana, Nafisatul; Anni, Catharina Tri (Universitas Negeri Semarang, 2016)
Abstract The purpose of this study was to describe the use of software in management IKMS® BK in SMA Semarang with descriptive research. In this thesis discusses the BK management planning, in the sphere of software IKMS® is in how the software operational IKMS® by teachers BK, obstacles encountered, IKMS® software weaknesses, advantages IKMS® software. The research location is in the district high schools in Semarang. Samples are schools that use software IKMS® as a need assessment instruments and analysis. Respondents are school counselors and school personnel as a data source support. The technique of collecting data using interviews, observation, and documentation. The validity of the data used in this research is data triangulation.Results of research in the field indicates that planning in the management of BK are in accordance with the procedure, there is no constraint in operationalising software IKMS® by BK teachers, except in the input data is quite long. There are some disadvantages of IKMS® as students answer is still questionable honesty, need assessment results only acquire data from students' nonverbal course, use a long time and the means used quite a lot. The advantages of the software are to assist in the administration IKMS® BK teachers.